Investigating interactions between early life stress and two single nucleotide polymorphisms in HSD11B2 on the risk of schizophrenia. (October 2015) - Debost, Jean-Christophe; Petersen, Liselotte; Grove, Jakob; Hedemand, Anne; Khashan, Ali; Henriksen, Tine; Mors, Ole; Hollegaard, Mads; Hougaard, David; Nyegaard, Mette; Børglum, Anders; Mortensen, Preben Bo
Highlights: A two-stage design was applied in the study, with:. A nationwide, population-based cohort study investigating the effects of early life stress on the risk of developing schizophrenia. We found a significantly increased risk of schizophrenia after exposure to stress within the first 2 years of life. No increased risk of schizophrenia was found after stress exposure during pregnancy. A nested case-control study with information on genotype from a cortisol-regulating gene ( HSD11B2 ). We investigated the risk of schizophrenia after early life stress according to genotypes, and found that individuals hetero- or homozygous for the minor A allele of the exonic SNP rs5479 had a significantly increased risk after exposure in the period 3–9 years after birth. This risk was significantly higher than for individuals homozygous for the major C allele of rs5479. No interaction was found between any of the SNPs and exposure during pregnancy. Summary: Background : To examine the risk of schizophrenia in a Danish population after exposure to early life stress, and whether this risk is modified by DNA sequence variation, specifically two single nucleotide polymorphisms (SNPs) (rs5479 and rs56303414) from the gene HSD11B2 . This gene encodes the enzyme 11-β hydroxysteroid dehydrogenase type 2 which converts active cortisol into inactive cortisone. Methods : A two-stage analysis involving (1) a population-based cohort study, and (2) a nested case-control study using genotype information. Stage 1 included 1, 141, 447 people; here, we calculated incidence rate ratios (IRR) for the risk of schizophrenia among children of mothers who experienced loss or serious illness of close relatives before, during, and after pregnancy. In stage 2, we genotyped rs5479 and rs56303414 among 1275 schizophrenia cases and 1367 controls, and investigated interactions between genotypes and early life stress on the risk of schizophrenia. Results : In stage 1, no increased risk of schizophrenia was found in offspring after exposure during pregnancy, but offspring exposed to early life stress at age 0–2 years had a significantly increased risk of schizophrenia (adjusted IRR 1.18, 95% confidence interval 1.07–1.31). For rs5479, the minor allele was nucleotide A, and the major allele was nucleotide C. No interaction was found between rs5479 and exposure during pregnancy. Individuals with the minor A allele of rs5479, however, had a significantly increased risk of schizophrenia after exposure to early life stress at age 3–9 years (adjusted IRR 2.06, 1.04–4.06). No interaction was found between rs56303414 and exposure in any of the time periods. Conclusion : No association was found between exposure to early life stress during pregnancy and schizophrenia in the offspring investigated, whereas individuals exposed to early life stress within the first two years of life had an increased risk. No interaction was found between HSD11B2 and exposure during pregnancy, but individuals with the A allele of rs5479 had an increased risk of schizophrenia after exposure at age 3–9 years.